(3GdeUGQa GdGSdGejI (B:s (3ebQQGJ dLfI HGRd (B- (3JOjGJ GdYhdeI (B- (3GSJQGJjLjI ehGLgJgG (B/s - (3NUGhfg, GMeO SdjeGfs ((3GQHO(B: s (3YGde GdcJH GdMOjK(B, s, 2008)
(3GdYhdeI GdeGdjI hGdGbJUGOjI , GdeUGQa GdESdGejI , ebQQGJ dLfI HGRd (B2 (3hCKQgG Ydi GdeUGQa GdGSdGejI , GdaUd GdQGHY Cge GdJMOjGJ dJj JhGLg GdeUGQa GdGSdGejI aj Xd GdYhdeI GdeGdjI , GSJQGJLjI Yed GdeUGQa GdGSdGejI aj ehGLgI JMOjGJ GdYhdeIs
(3eQGLY U(B. 313s
Keywords: (3GbJUGO eGdjs; (3Hfhc GSdGejIs